Antigua and Barbuda. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Antigua and Barbuda during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainability, resilience to climate change, good agricultural practices, technology, innovation, labeling, packaging , health and safety through the Codex Alimentarius. Likewise, work was done on the agro-processing of agricultural products, on the sustainable use of the land and on local markets. Finally, support was given to the inclusion of rural women, vermicomposting, vermiculture and the chili value chain.